Different answers to different audiences: effects of social context on the accuracy-informativeness trade-off. Issue 7 (9th August 2018) - Martín-Luengo, Beatriz; Shtyrov, Yury; Luna, Karlos; Myachykov, Andriy
ABSTRACT: Research on conversational exchanges shows that people attempt to optimise their responses' relevance when they definitely know the correct answer (e.g., "What time is it?"). However, such certainty is often unavailable while speakers may still be under social pressure to provide an answer. We investigated how social context influences the informativeness level when answering questions under uncertainty. In three experiments, participants answered difficult general-knowledge questions placed in different social contexts (formal vs. informal). Participants generated their answers, then they were presented with a given context, and decided on the number of alternative responses they wanted to provide (single, with one alternative vs. plural, with several alternatives) and whether the answer should be reported or withheld (report option). Participants reported more answers in the informal context. In the formal context, single answers were preferred, and they were more frequently reported. We conclude that social context influences the level of informativeness in a conversation, affecting achievable accuracy. Our results also show the joint influence of the confidence and the social context on willingness to share information.